Faktor Risiko Kelainan Kadar Eritrosit pada Pengendara Ojek Motor Online di Kawasan Industri Tanjung Mas Kota Semarang: Risk Factors for Abnormal Erythrocyte Levels in Online Motorcycle Taxi Riders in the Tanjung Mas Industrial Area, Semarang City - Lilik Setyowatiningsih; Qurrotu A’yuni Auliya; Ririh Jatmi Wikandari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Industrial activities and motor vehicle exhaust gases significantly contribute to air pollution; the longer the exposure to pollutants, the higher the pollutant levels in the blood. Online motorcycle taxi drivers in industrial areas have a high risk of being exposed to pollutants. This study aims to determine the risk factors that affect erythrocyte levels in online motorcycle taxi drivers in the industrial area of ​​Semarang City. The method used is analytic observational with a cross-sectional approach. Of 55 respondents, 41 had normal erythrocyte levels, and 14 had above-normal erythrocyte levels (polycythemia). Chi-square test results on smoking status, educational status, working length, and knowledge did not show a significant relationship (p <0.05) on erythrocyte levels in online motorcycle taxi drivers in industrial areas, Semarang City. The conclusion of this study, there is no significant relationship between smoking status, educational status, length of time working, and knowledge of the erythrocyte levels of online motorcycle taxi drivers in the Tanjung Emas industrial area, Semarang City.